Memory accuracy after 20 years for interviews about child maltreatment - Wu, Yuerui (Child maltreatment, 2023)
When adults allege childhood victimization, their long-term memory comes under scrutiny. This scrutiny can extend to the adults? memory of childhood interviews. The concerns raise important theoretical and applied issues regarding memory for long-past discussions of child maltreatment and trauma. In this longitudinal study, 104 adults, who as children (ages 3?15 years) were interviewed in child maltreatment investigations (Time 1), were questioned 20 years later (Time 2) about the Time 1 interviews. Verbatim documentation from Time 1 permitted scoring of memory accuracy. A subset of the participants (36%) reported no memory for the Time 1 interviews. Of the 64% who remembered being interviewed at Time 1, those who had been adolescents at Time 1 remembered the forensic interview discussion about abuse incidents better than discussion about general psychological issues. Adult trauma symptoms were associated with more accurate memory for interview content that directly concerned abuse experiences but not for non?abuse-specific information. Findings indicate that the veracity of adults? long-term memory for clinical/forensic conversations about childhood maltreatment depends on age at interview, interview content, and traumatization factors. Implications are discussed.